دور الأدب العربي النيجيري في توفير الأمن والأمان في نيجيريا: The Role Of Nigerian Arabic Literature in Providing Security And Safety in Nigeria - Zakariyya Muhammad Abdullahi; Haruna Abubakar Haruna (Journal of Arabic Language Teaching, 2024)
This study aims to expand the scientific and intellectual level in the Arab literary field by highlighting the significant role played by Nigerian Arabic literature in providing security and safety in the Dear Nigerian Homeland. The approach followed in this thesis is the descriptive-analytical approach, as it is more suitable for this study. The study dealt with the doctrines of the literati about the function of literature in society, pointing out that literature has many doctrines. Then, she talked about the literary environment of Nigeria before the colonists came to it, pointing out that it was a beautiful academic environment. She also spoke about Nigerian Arabic literature providing security and safety in Nigeria, noting that it played a considerable role in various literary fields, from poetry to speeches and writing.